1996
DOI: 10.1021/np960231c
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Oenothein B as the Active 5-α-Reductase-Inhibiting Principle of the Folk Medicine Epilobium parviflorum

Abstract: Several extracts from Epilobium parviflorum, a plant used in Central Europe for the treatment of prostate disorders, were evaluated in a biochemical assay with 5-alpha-reductase. The aqueous extract displaying inhibition of the enzyme was analyzed, the fraction responsible for this activity was purified, and the active compound identified as a macrocyclic tannin, oenothein B (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 22 publications
1
32
0
1
Order By: Relevance
“…Flow cytometry analysis indicated that the antiproliferative effect could be ascribed to an inhibition of the progression of the cell cycle, in agreement with our previous results obtained with the extracts in toto [19]. The antiproliferative action of the nonpolar fraction may be ascribed to flavonoids, macrocyclic ellagitannins, or sterols identified in these extracts [20,21]. In a previous study [14], flavonoids and sitosterol derivates were detected in the ethyl acetate phase (nonpolar fraction).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Flow cytometry analysis indicated that the antiproliferative effect could be ascribed to an inhibition of the progression of the cell cycle, in agreement with our previous results obtained with the extracts in toto [19]. The antiproliferative action of the nonpolar fraction may be ascribed to flavonoids, macrocyclic ellagitannins, or sterols identified in these extracts [20,21]. In a previous study [14], flavonoids and sitosterol derivates were detected in the ethyl acetate phase (nonpolar fraction).…”
Section: Discussionsupporting
confidence: 90%
“…This may thus explain the greater potency of E. rosmarinifolium in inhibiting cell proliferation and, at the same time, also suggests that oenothein B may play a relevant role in such an antiproliferative effect. Oenothein B is a macrocyclic ellagitanin, a dimer of the tellimagrandin I unit, that can inhibit the activity of 5·-reductase and aromatase [20,24]. Oenothein B has been shown to have antitumor effects in vivo in mice [22] and to inhibit cellular growth in vitro principally because of decreased cell viability [23,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In past, Epilobium species have used as a preventative measure for benign prostatic hyperplasia (BPH); [41][42][43][44] and many reports suggest of plant possessing anti-proliferative, anti-inflammatory and antioxidant activities. [45][46][47][48][49][50][51][52] More specifically, Epilobium extracts have shown noticeable effects on activities of several key enzymes including 5α-reductase and aromatase, 53,54 caspase 3 55 and metaloproteinases.…”
Section: Canadian Willow Herbmentioning
confidence: 99%